Muscle Hypertrophy in a Newly Developed Resistance Exercise Model for Rats - Al-Sarraf, Hameed; Mouihate, Abdeslam (Frontiers in Physiology, 2022)
Clinical evidence suggests that resistance exercise exerts health benefit. The mechanisms underlying such health benefits is largely explored in experimental animals. Available experimental models have several shortcomings such as the need for noxious stress stimuli that could affect the physiological readouts. In this study, we describe a simple-to-use experimental model of resistance exercise with minimal stress to the animals. In this resistance exercise, rats pull pre-determined weights using a tunnel and pulley system. We show that resistance-exercised rats developed a larger pulling strength when compared to those seen in either control rats or in rats subjected to traditional treadmill exercise. Histological examination revealed that resistance exercise led to a larger fiber cross-sectional area in the plantaris muscle, but not in the gastrocnemius or the soleus muscles. Similarly, the percentage of type-II muscle fibers in the plantaris was increased in resistance exercised rats when compared to those seen in plantaris muscles of either control or treadmill-exercised rat groups. Furthermore, this resistance exercise led to a significant increase in the expression levels of the phosphorylated protein kinase B; a marker of muscle hypertrophy in the plantaris muscle. Such effects were not seen in treadmill-trained rats. In conclusion, we developed an experimental model that can be amenable for experimental exploration of the mechanisms underlying the beneficial effects of resistance exercise. We further provide evidence that this resistance exercise model enhanced muscle strength and muscle hypertrophy.